MODERN HYPOLIPIDEMIC THERAPY (LITERATURE REVIEW) - Y.V.Botsiurko (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
Statins are highly effective drugs for the prevention and treatment of atherosclerotic cardiovascular diseases. With prolonged use, they can reduce cardiovascular risk by reducing the cholesterol content of low-density blood lipoproteins (LDL-C). However, even with a combination of a high-dose regimen of statin therapy with the use of ezetimib, it is not always possible to achieve the targets of LDL-C according to modern recommendations. Thus, there is an unmet clinical need for new lipid-lowering drugs that can lower cholesterol levels of low-density lipoproteins and other atherogenic lipoproteins. Over the past decade, a number of new drugs have been developed to treat dyslipidemia, which is reflected in this review. Key words: LDL cholesterol, statins, inclisiran, PCSK9 inhibitors, bempedoic acid.